Learning Technology in Elementary School - Sa'odah Sa'odah; Nury Yuniasih; Yuyun Dwi Haryanti (AL-ISHLAH: Jurnal Pendidikan, 2022)
Teachers currently face greater challenges than the previous era, where teachers are required to utilize technology in the learning process. This article provides a comprehensive overview of the technology used by primary school teachers. This study uses a qualitative descriptive method that explains what learning technologies are used by elementary school teachers. The instrument in this study was a questionnaire about the learning technology used and its strengths and weaknesses. The results showed 68% of the 335 teachers used the video call application via Whatsapp to create classes, Microsoft Power Point to create online learning media, Microsoft Word to create online student worksheets, Kinemaster to make learning videos, Whatsapp Group for online assignments, and Google Form for online evaluation. The advantage of this technology is that it is the only learning tool that is the most effective and efficient during this pandemic, while the disadvantage lies in the high costs involved in providing internet data packages. It is highly recommended for teachers to develop effective and efficient learning technology.